Evaluation of life cycle energy, economy and CO2 emissions for biomass chemical looping gasification to power generation. (October 2021) - Mohamed, Usama; Zhao, Ying-jie; Yi, Qun; Shi, Li-juan; Wei, Guo-qing; Nimmo, William
Abstract: A life cycle energy use, CO2 emissions and cost input evaluation of a 650 MW Biomass Chemical Looping Gasification Combined Cycle (BCLGCC) and a Biomass/Coal Integrated Gasification Combined Cycle (BIGCC/CIGCC) power generation plants with and without (w/o) CO2 capture & storage (CCS) are analysed. These were then compared to coal/biomass combustion technologies. The life cycle evaluation covers the whole power generation process including biomass/coal supply chain, electricity generation at the power plant and the CCS process. Gasification power plants showed lower energy input and CO2 emissions, yet higher costs compared to combustion power plants. Coal power plants illustrated lower energy and cost input; however higher CO2 emissions compared to biomass power plants. Coal CCS plants can reduce CO2 emissions to near zero, while BCLGCC and BIGCC plants with CCS resulted in negative 680 kg-CO2 /MWh and 769 kg-CO2 /MWh, respectively, which is due to the higher biomass utilization efficiency for BCLGCC compared to BIGCC hence less CO2 captured and stored. Regarding the total life cycle costs input (TLCCI), BCLGCC with and without CCS equal to 149.3 £/MWh and 199.6 £/MWh, and the total life cycle energy input (TLCEI) for both with and without CCS is equal to 2162 MJ/MWh and 1765 MJ/MWh, respectively. Graphical abstract: Image 1